Baseline characteristics of the Korean genetic cohort of inherited cystic kidney disease - Jeong Min Cho; Hayne Cho Park; Jin Woo Lee; Hyunjin Ryu; Yong Chul Kim; Curie Ahn; Kyu-Beck Lee; Yeong Hoon Kim; Seungyeup Han; Yaerim Kim; Eun Hui Bae; Hee Gyung Kang; et al. (The Korean Society of Nephrology, 2023)
Background Identifying genetic mutations in individuals with inherited cystic kidney disease is necessary for precise treatment. We aimed to elucidate the genetic characteristics of cystic kidney disease in the Korean population. Methods We conducted a 3-year prospective, multicenter cohort study at eight hospitals from May 2019 to May 2022. Patients with more than three renal cysts were enrolled and classified into two categories, typical autosomal dominant polycystic kidney disease (ADPKD) and atypical PKD. We identified the clinical characteristics and performed a genetic analysis using a targeted gene panel. Results A total of 725 adult patients were included in the study, of which 560 (77.2%) were diagnosed with typical ADPKD and 165 (22.8%) had atypical PKD. Among the typical ADPKD cases, the Mayo imaging classification was as follows: 1A (55, 9.9%), 1B (149, 26.6%), 1C (198, 35.8%), 1D (90, 16.3%), and 1E (61, 11.0%). The atypical PKD cases were classified as bilateral cystic with bilateral atrophic (31, 37.3%), lopsided (27, 32.5%), unilateral (nine, 10.8%), segmental (eight, 9.6%), bilateral cystic with unilateral atrophic (seven, 8.4%), and asymmetric (one, 1.2%). Pathogenic variants were found in 64.3% of the patients using the ciliopathy-related targeted gene panel. The typical ADPKD group demonstrated a higher discovery rate (62.3%) than the atypical PKD group (41.8%). Conclusion We present a nationwide genetic cohort's baseline clinical and genetic characteristics for Korean cystic kidney disease.